2015
DOI: 10.1080/13678868.2015.1122895
|View full text |Cite
|
Sign up to set email alerts
|

The influence of learning activity on low-skilled workers’ skill improvement in the South Korean manufacturing industry

Abstract: The main purpose of this study was to explore how low-skilled worker's learning activity influences skill improvement. Using a unique 2007 Human Capital Corporate Panel dataset from the South Korean manufacturing industry, we operationalize skill improvement over time among low-skilled workers. A worker is classified as 'low skilled' if he or she has a low education level and poor technical skills. Regression models show that lowskilled workers' informal learning positively influences their skill improvement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Differences in country labour costs reflect currency evaluation and cost‐of‐living differences, as well as educational attainment and skill levels, in that lower educational attainment and skills reflect lower labour cost economies. Several researchers have shown that training can help low‐skilled employees increase their skills and earnings (Prince, 2008; Washington State Board for Community and Technical College, 2005) and that the impact of training is stronger among low‐skilled rather than higher‐skilled employees (Kim, Hawley, Cho, Hyun, & Kim, 2016). Budria and Pereira (2007) found that less educated workers experience larger returns from training compared to well‐educated workers.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Differences in country labour costs reflect currency evaluation and cost‐of‐living differences, as well as educational attainment and skill levels, in that lower educational attainment and skills reflect lower labour cost economies. Several researchers have shown that training can help low‐skilled employees increase their skills and earnings (Prince, 2008; Washington State Board for Community and Technical College, 2005) and that the impact of training is stronger among low‐skilled rather than higher‐skilled employees (Kim, Hawley, Cho, Hyun, & Kim, 2016). Budria and Pereira (2007) found that less educated workers experience larger returns from training compared to well‐educated workers.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…The training course is divided into two 1-week didactic sessions that are structured around short lectures, exams, case study group assignments, interactive learning exercises, and daily homework assignments. The use of case studies and learning exercises help to reinforce learning [ 15 17 ]. The mission of the case study teams is to enhance collaboration and communication.…”
Section: Case Presentationmentioning
confidence: 99%
“…The faculty used daily quizzes and group case study assignments to measure the transfer of “content” to the participants. Content transfer is an important component of human resource development as it indicates if participants are acquiring new knowledge and skills and the likelihood of application of that knowledge and those skills once returned to the work site [ 26 , 17 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…-informal learning (Kim et al, 2016); -personal involvement (Fletcher, 2016); -knowledge transfer (Argote and Fahrenkopf, 2016); -absence of obstacles for know-how (rationalization); -leadership, accumulation and exchange of knowledge (Shin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%